Is glucose-6-phosphate dehydrogenase deficiency more prevalent in Carrion's disease endemic areas in Latin America? - Mazulis F. (2015)
Glucose-6-phosphate dehydrogenase (G6PD) is a cytoplasmic enzyme with an important function in cell oxidative damage prevention. Erythrocytes have a predisposition towards oxidized environments due to their lack of mitochondria, giving G6PD a major role in its stability. G6PD deficiency (G6PDd) is the most common enzyme deficiency in humans; it affects approximately 400 million individuals worldwide. The overall G6PDd allele frequency across malaria endemic countries is estimated to be 8%, corresponding to approximately 220 million males and 133 million females. However, there are no reports on the prevalence of G6PDd in Andean communities where bartonellosis is prevalent.